The sadness of Bulgaria (2012)
There is a significant positive statistical connection between GDP per capita and the satisfaction rate. However, Bulgaria, being a middle income economy, is one of the saddest places on Earth. We try to identify possible reasons for this phenomenon and we put forward some policy implications. The evolution of fertility rates, income per capita and income distribution during the democratic era help to understand the Bulgarian sadness.